2019
DOI: 10.1063/1.5100064
|View full text |Cite
|
Sign up to set email alerts
|

Fluidity enhancement of hard-to-fluidize nanoparticles by mixing with hydrophilic nanosilica and fluid catalytic cracking particles: Experimental and theoretical study

Abstract: As a low-cost method, hydrophilic SiO2 nanoparticles (NPs) and fluid catalytic cracking (FCC) coarse particles were used as assistant materials to improve the fluidity of Al2O3 and TiO2 hard-to-fluidize nanopowders. To decrease the strong electrostatic forces between the hydrophilic nanopowders, prepared samples were fluidized in the presence of methanol vapor. Results revealed that the amount of SiO2 NPs, increased from 5 to 50 wt. %, has a beneficial effect on the fluidization quality of the binary (hard-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…2(c), are distributed between the CNTs. It can be inferred that strong electrostatic forces of attraction developed at the contact points between the SiO 2 NPs and CNT particles due to contact charging [19,20,23,25,26]. The easy-fluidizable SiO 2 NPs become carriers of the CNT particles, which improves the fluidity behavior.…”
Section: Fluidizability Of Pure Cnt + Sio 2 Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…2(c), are distributed between the CNTs. It can be inferred that strong electrostatic forces of attraction developed at the contact points between the SiO 2 NPs and CNT particles due to contact charging [19,20,23,25,26]. The easy-fluidizable SiO 2 NPs become carriers of the CNT particles, which improves the fluidity behavior.…”
Section: Fluidizability Of Pure Cnt + Sio 2 Npsmentioning
confidence: 99%
“…The NPs with better fluidization behavior, such as hydrophobic silica, are the most common auxiliary additives to enhance the fluidization ability of hard-to-fluidized NPs [20]. By adding the optimized amounts of the mentioned assistant materials, U mf will decrease while the bed expansion increases [19,20,23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fluidization of CaO adsorbents (in fine and pellet scales) in fluidized bed reactor under realistic conditions has not been comprehensively investigated yet. Previous studies have reported the heterogeneous fluidity quality of fine CaO particles in fluidized bed due to the nature of CaO, a subset of Geldart C group materials [92][93][94], even though several internal methods have been proposed to improve CaO-based particle fluidity at lab-scale experiments [48,49,95,96]. It is north worthy that, in addition to promising cyclic activity and morphological properties, the complete fluidization of CaO adsorbents is required to employ the CaL process in practical and industrial applications.…”
Section: Outlooks Of Cao Adsorbents At Cal Processmentioning
confidence: 99%
“…In order to minimize the deposition of carbon and enhance the lifecycle of catalysts, it may become necessary to develop unique methods of changing the ZSM-5 zeolites surface elements. According to Tahmasebpoor, Rahimvandi Noupoor, and Badamchizadeh [2], it is hoped that the inclusion of metals similar to those used in fluid catalytic cracking (FCC) catalysts would be effective. Synthesis and use of certain mix crystal zeolites with unique features in the petroleum refinery may shed light on the possibility of bio-oil catalytic cracking.…”
Section: Introductionmentioning
confidence: 99%